The art of Horizon zero dawn - Davies, Paul (Game journalist); Titan Books (Firm) (London : Titan Books, 2017)
"The Art of Horizon Zero Dawn takes you through the vast and vibrant world of Guerrilla Games' newest title, featuring detailed sketches and gorgeous concept artwork as well as insight from the artists and creators. From magnificient cities and lush plains, to the diverse cultures of the tribes and the amazing machines that roam the lands, this stunning visual companion is the ultimate guide to the creation of a world as beautiful as it is dangerous."--Back cover.
Nora -- Carja -- Oseram -- Bandits -- Banuk -- Eclipse -- Machines -- Ruins.
Chiefly illustrations.
Keywords: Horizon zero dawn (Video game) -- Pictorial works; Video games -- Design -- Pictorial works; Computer art -- Pictorial works; Computer animation; Computer art